Experiences of individuals with various sexual orientations with healthcare professionals: integrative literature review. - Krnel, Tilen Tej; Skela-Savič, Brigita (Obzornik Zdravstvene Nege, 2020)
Introduction: Individuals may belong to different sexual minorities. Such a personal circumstance should not influence the quality of healthcare. Yet, many face discrimination due to their sexual orientation, while the healthcare system is typically heteronormative. The objective of this integrative review was to provide a synthesis of research evidence on the experiences of lesbian, gay, bisexual and transgender (LGBT) individuals with healthcare professionals. Methods: An integrative literature review was employed, and codes and categories were identified. A literature search was performed in the databases Springer Link, SAGE, CINAHL, Academic Search Elite and MEDLINE. The key words used were: "experiences", "healthcare", "gay patient experiences", "gay", "lesbian", "homosexual", "bisexual" and "transgender". Primary sources were selected according to inclusion and exclusion criteria. Thematic analysis was conducted with an open coding of the results of selected sources. Results: A total of 6,839 studies were screened from June to August 2018 and 14 (published between 2009 and 2017) were selected for the final analysis. The results yielded 41 codes, combined into two categories termed: 'Positive experiences of LGBT individuals with healthcare professionals' and 'Negative experiences of LGBT individuals with healthcare professionals'. Discussion and conclusion: The experiences of LGBT individuals with healthcare professionals are ambivalent. Although positive experiences prevail, negative ones should not be overlooked as they are derived from heteronormativity and sometimes even prejudice and homophobia. Healthcare professionals need cultural competences which reflect the developments in a society and the needs of its individuals.